Effect of chitosan/inorganic nanomaterial scaffolds on bone regeneration and related influencing factors in animal models: A systematic review - Guo, Anjie; Zheng, Yi; Zhong, Yu; Mo, Shuixue; Fang, Shanbao (Frontiers in Bioengineering and Biotechnology, 2022)
Bone tissue engineering (BTE) provides a promising alternative for transplanting. Due to biocompatibility and biodegradability, chitosan-based scaffolds have been extensively studied. In recent years, more and more inorganic nanomaterials have been utilized to modify the performance of chitosan-based materials. In order to ascertain the impact of chitosan/ inorganic nanomaterial scaffolds on bone regeneration and the related key factors, this study presents a systematic comparison of various scaffolds in the calvarial critical-sized defect (CSD) model. Four electronic databases were searched without publication date or language restrictions up to April 2022. The Animal Research Reporting of In Vivo Experiments 2.0 guidelines (ARRIVE 2.0) were used to assess the quality of included studies. Moreover, the risk of bias (RoB) was evaluated via the Systematic Review Centre for Laboratory Animal Experimentation (SYRCLE) tool. After the screening, 22 studies were selected. None of these studies achieved high quality or had a low RoB. In the available studies, scaffolds reconstructed bone defects in radically different extensions. Several significant factors were identified, including baseline characteristics, physicochemical properties of scaffolds, surgery details, and scanning or reconstruction parameters of micro-computed tomography (micro-CT). Further studies should focus on not only improving the osteogenic performance of the scaffolds but also increasing the credibility of studies through rigorous experimental design and normative reports.